2022
DOI: 10.1111/apt.16964
|View full text |Cite
|
Sign up to set email alerts
|

Association of golimumab trough concentrations during maintenance with clinical, biological, endoscopic and histologic remission in patients with ulcerative colitis

Abstract: Summary Background Optimal golimumab concentration thresholds for important outcomes during maintenance are lacking. Aims To investigate the association of golimumab trough concentrations during maintenance with key outcomes, including endoscopic and histologic remission, and long‐term event‐free persistence with golimumab, in patients with UC. Methods This multi‐centre, cross‐sectional study included patients with UC on golimumab maintenance recruited either in remission or during a flare. Colonoscopy was sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Editorial: golimumab thresholds to achieve stringent medium-and long-term therapeutic outcomes in patients with ulcerative colitis-Author's reply I thank Mantzaris and Papamichael for their comments and interest in our study evaluating the exposure-response relationship of serum golimumab trough concentrations (GTC) during maintenance therapy with outcomes, including endoscopic healing and histologic remission, in patients with ulcerative colitis (UC). 1,2 I agree that the main limitation of our study is the lack of longitudinal proactive or reactive therapeutic drug monitoring (TDM) to confirm the usefulness of these GTC thresholds in the management of patients with UC. However, the study makes it clear that higher GTCs obtained during maintenance were indicative of future efficacy outcomes.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 58%
See 2 more Smart Citations
“…Editorial: golimumab thresholds to achieve stringent medium-and long-term therapeutic outcomes in patients with ulcerative colitis-Author's reply I thank Mantzaris and Papamichael for their comments and interest in our study evaluating the exposure-response relationship of serum golimumab trough concentrations (GTC) during maintenance therapy with outcomes, including endoscopic healing and histologic remission, in patients with ulcerative colitis (UC). 1,2 I agree that the main limitation of our study is the lack of longitudinal proactive or reactive therapeutic drug monitoring (TDM) to confirm the usefulness of these GTC thresholds in the management of patients with UC. However, the study makes it clear that higher GTCs obtained during maintenance were indicative of future efficacy outcomes.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 58%
“…Conversely, in a real‐life study, 71% of patients with dose escalation during maintenance regained response and persisted on golimumab at last follow‐up 6 . In our current study the golimumab dose was escalated in five patients due to secondary loss of response during maintenance 2 . Although this was not a TDM‐guided reactive dose optimization, as the investigators were not aware of the GTCs, four patients regained response and avoided discontinuation of golimumab at the last follow‐up.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…[PMS] ≤2], combined clinical-biomarker remission (PMS ≤2 and faecal calprotectin ≤250 μg/g), endoscopic healing (Mayo Endoscopic Subscore = 0), histological remission (Geboes Index ≤2) 'disease clearance' (defined as combined clinical biomarker, endoscopic and histological remission) and long-term treatment persistence. 8 Patients who achieve the aforementioned targets had significantly higher median GTCs than patients who failed. Golimumab thresholds (area under the curve) of 0.85 (0.76), 1.90 (0.76), 2.29 (0.75), 1.79 (0.68), 2.29 (0.72) and 1.56 (0.71) μg/ml were associated with clinical remission, combined clinical-biochemical remission, endoscopic healing, histological remission, disease clearance and uneventful long-term treatment persistence, respectively.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…Taxonera et al performed a multicenter, cross‐sectional, cohort study in 52 patients with ulcerative colitis (UC) treated with golimumab and found positive associations between maintenance golimumab trough concentrations (GTCs) with several stringent sole and composite outcomes, such as clinical remission (Partial Mayo Score [PMS] ≤2], combined clinical‐biomarker remission (PMS ≤2 and faecal calprotectin ≤250 μg/g), endoscopic healing (Mayo Endoscopic Subscore = 0), histological remission (Geboes Index ≤2) ‘disease clearance’ (defined as combined clinical biomarker, endoscopic and histological remission) and long‐term treatment persistence 8 . Patients who achieve the aforementioned targets had significantly higher median GTCs than patients who failed.…”
mentioning
confidence: 99%